2020
DOI: 10.1186/s12909-020-02277-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mixing international and domestic students on competency learning in small groups in undergraduate medical education

Abstract: Background Medical curricula are increasingly internationalized, with international students being mixed with domestic students in small group learning. Small group learning is known to foster competency learning in undergraduate medical education, specifically Communication, Collaboration, Leadership, and Professionalism. However, it is unclear what happens with the learning of competencies when international students are introduced in small groups. This study explores if students in internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
4
1
Order By: Relevance
“…The other side of these assessment results is that those TLCs show relatively lower competencies performance than TLC SC and TLC GH. In contrast to the previous study where we showed that the two English taught TLCs showed higher competencies assessment results than two Dutch taught TLCs [ 21 ], we now found that the Dutch TLCs had better written test scores than two English TLCs in the first year. There seems to be a clear trade-off between the focus on competencies or knowledge development, especially in the first year.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The other side of these assessment results is that those TLCs show relatively lower competencies performance than TLC SC and TLC GH. In contrast to the previous study where we showed that the two English taught TLCs showed higher competencies assessment results than two Dutch taught TLCs [ 21 ], we now found that the Dutch TLCs had better written test scores than two English TLCs in the first year. There seems to be a clear trade-off between the focus on competencies or knowledge development, especially in the first year.…”
Section: Discussioncontrasting
confidence: 99%
“…Table 3 shows that students’ competencies performance became higher at the end of the second year in all TLCs, which is similar to what is observed earlier in the competencies result of the shared program [ 21 ]. The percentages of FOT for all competencies together varied from 16.21% to 41.63% and the percentages of FOT became higher at the end of the second year although there were some variations over time.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The possible influencing factors included the lack of language proficiency, familiarity with the cultural environment, and experience in collaborative groups [ 18 ]. However, many studies have found that mixed ethnic groups enhance student interactions across diverse boundaries and that students in such groups receive better performance evaluations than students in homogenous groups [ 4 , 5 , 16 ]. What remains unknown is how multiethnic groups affect student learning outcomes or group interactions in a PBL learning model.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the positive effects of informal relationship formation based on homophily, it may also lead to negative effects on learning, especially when the clustering takes place based on background and academic achievement. In international settings, for instance, it is known that both international and domestic students tend to form relationships mostly with peers of the same nationality [ 30 , 31 ], while the diversity of students’ backgrounds in classrooms or groups is known to benefit students’ academic performance [ 38 ]. Another negative side effect of homophily may be that low achievers have more problems building their own social groups because they seem to be excluded from the high achievers’ peer relationships to some extent [ 39 ].…”
Section: Introductionmentioning
confidence: 99%